2012
DOI: 10.1063/1.3675981
|View full text |Cite
|
Sign up to set email alerts
|

Control of magnetic properties of MnBi and MnBiCu thin films by Kr+ ion irradiation

Abstract: Mn52Bi48 (15 nm) and Mn54Bi24Cu21 (15 nm) thin films were prepared by the magnetron sputtering and vacuum annealing at 350 °C, and the variations of their structures and magnetic properties with 30 keV Kr+ ion irradiation were studied. The MnBi and MnBiCu films exhibited saturation magnetizations Ms of 180 emu/cc and 210 emu/cc, the coercivities Hc of 10 kOe and 3.4 kOe, respectively. The Ms and Hc of the MnBi abruptly vanished by the irradiation of ion dose at 3 × 1014 ions/cm2, while those of the MnBiCu film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, high-temperature heat treatment at 850 C is required to synthesize the L1 CrPt , which is a problem for the practical application. In this paper, MnBiCu thin film is discussed as an alternative material to the CrPt , since the MnBiCu film also exhibits a large perpendicular anisotropy and is fabricated by a low process temperature of less than 400 C [13]- [15]. By local ion irradiation on the MnBiCu thin film, bit patterned structures are fabricated and their magnetization reversal processes are investigated by magnetic force microscope observations.…”
Section: Introductionmentioning
confidence: 99%
“…However, high-temperature heat treatment at 850 C is required to synthesize the L1 CrPt , which is a problem for the practical application. In this paper, MnBiCu thin film is discussed as an alternative material to the CrPt , since the MnBiCu film also exhibits a large perpendicular anisotropy and is fabricated by a low process temperature of less than 400 C [13]- [15]. By local ion irradiation on the MnBiCu thin film, bit patterned structures are fabricated and their magnetization reversal processes are investigated by magnetic force microscope observations.…”
Section: Introductionmentioning
confidence: 99%
“…We reported that 30 keV Kr + ion implantation altered the magnetism of CrPt 3 [15][16][17][18], MnAl [19], MnGa [19][20][21][22], and MnBiCu [23] from ferromagnetic to paramagnetic according to the change of the crystal structure from the ordered to disordered phase. All of these materials exhibit a strong perpendicular magnetic anisotropy, which is an essential property for high-density BPM.…”
Section: Introductionmentioning
confidence: 99%